Subclinical Hypothyroidism in Children and Adolescents: a single-center retrospective study - Monteiro, Ana Margarida (2018)
Introduction: The ideal management of subclinical hypothyroidism, particularly the mild form, remains unclear. Our objectives were to describe the clinical management of subclinical hypothyroidism in children and adolescents and the natural course of the disease with conservative management. Material and Methods: We retrospectively analyzed clinical records of patients, under the age of 18 years, referred to our pediatric endocrinology department due to subclinical hypothyroidism between 2009 and 2014, with ≥1 year of followup. Patients under one month of age and with TSH (thyroidstimulating hormone) levels <5 uUI/mL were excluded. Subclinical hypothyroidism was considered when TSH levels >5 uUI/mL with a normal serum free thyroxine. Mild and severe subclinical hypothyroidism were defined when TSH was <10 uUI/mL and ≥10 uUI/mL, respectively. Results: We included 69 patients (62.3% girls) with a median age at diagnosis of 8.0 [(25th percentile-75th percentile (P25-P75): 4.75-11.0)] years. Most of the patients (80.6%) were symptomatic and Hashimoto thyroiditis was the most frequent identified cause. A mild form of subclinical hypothyroidism was diagnosed in 79.7% of the patients. All patients with severe subclinical hypothyroidism initiated therapy with levothyroxine in contrast with 43.6% in the mild subclinical hypothyroidism group. Among patients not treated, 73.3% had TSH normalized after one year of follow-up and none progressed to overt hypothyroidism. Conclusion: The mild form of subclinical hypothyroidism was the most common typepf disease and, among patients managed conservatively, the majority presented normal thyroid function after one year of follow-up and none progressed to overt hypothyroidism. Our results reinforce the idea that, in most patients, subclinical hypothyroidism is a benign condition with a low risk of progression to overt thyroid dysfunction. However, further studies are needed to evaluate the potential long-term effects of the condition in untreated patients and to clarify the best clinical approach and follow-up strategy.